2006
DOI: 10.1590/s1516-89132006000500006
|View full text |Cite
|
Sign up to set email alerts
|

Lysine and metabolyzable energy requirements of lactating sows for subsequent reproductive performance

Abstract: The requirements of lactating sows for total lysine and metabolyzable energy (ME) to support subsequent reproduction performance were evaluated. One hundred and twenty sows were used. The treatments were constituted of eight diets (factorial arrangement of four levels of total lysine: 0.75, 0.90, 1.05 and 1.20%, and two levels of ME: 3,250 and 3,400 kcal ME/kg). There was interaction between lysine and ME on the plasma urea nitrogen (PUN), with linear decrease effect on level of 3,250 kcal ME/kg, and quadratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Taken together, lysine intake that ranged from 33.7 to 52.1 g/d met or supported piglet growth with no negative effects. The weaning weight of the piglets in the present study was similar to the results that observed by Touchette et al [32], Thaler et al [37], and Santos et al [38], who reported no improvement in litter performance with increasing lysine intake during lactation. In accordance with Knabe et al [30], the piglet weights at day 21 of lactation were not increased by feeding a corn-SBM-based diet with 0.9% lysine and they concluded that a 0.75% lysine diet met the nutrient needs of the sows or nutrient deficiency limited the sow's ability to respond to the higher lysine intake.…”
Section: )supporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, lysine intake that ranged from 33.7 to 52.1 g/d met or supported piglet growth with no negative effects. The weaning weight of the piglets in the present study was similar to the results that observed by Touchette et al [32], Thaler et al [37], and Santos et al [38], who reported no improvement in litter performance with increasing lysine intake during lactation. In accordance with Knabe et al [30], the piglet weights at day 21 of lactation were not increased by feeding a corn-SBM-based diet with 0.9% lysine and they concluded that a 0.75% lysine diet met the nutrient needs of the sows or nutrient deficiency limited the sow's ability to respond to the higher lysine intake.…”
Section: )supporting
confidence: 91%
“…In accordance with Knabe et al [30], the piglet weights at day 21 of lactation were not increased by feeding a corn-SBM-based diet with 0.9% lysine and they concluded that a 0.75% lysine diet met the nutrient needs of the sows or nutrient deficiency limited the sow's ability to respond to the higher lysine intake. In addition, the lack of response to increasing levels of lysine on litter performance (even with the addition of DL-methionine, L-threonine, and L-tryptophan to achieve balance in https://doi.org/10.5187/jast.2020.62.3.334 the diets) could be related to a lack of other limiting amino acids [32,38]. Thus, lysine intake during lactation met the minimum lysine requirement or induced amino acid imbalance of lactating sows and did not show any significant differences in litter growth as a result of the lysine effect.…”
Section: )mentioning
confidence: 99%
“…The weaning-to-estrus interval was shortened as the SID-Lys:ME ratio increased in Exp.2. Other studies have reported that increasing lysine intake did not affect weaning-to-estrus interval of sows [ 21 , 29 , 30 ]. These results may be due to the large lactation weight loss for sows rather than the low lysine intake.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive experience affects a series of reproductive performance parameters, such as calving rate (Buttram and Willham, 1989), litter size in dogs (Gavrilovic et al, 2008), weaning-toestrous interval in sows (Santos et al, 2006) and cattle (Melendez et al, 2008), lactation length and milk yield in cattle (Parra-Bracamonte et al, 2005). Reproductive experience also affects endocrine, neurochemical and behavioral responses.…”
Section: Introductionmentioning
confidence: 99%